A escrita rítmica de Juliano Pessanha - Sanchez, Francine Rodrigues (2017)
This research starts from a quest: how is it possible to conceive and conceptualize the rhythm in a prose contemporary literary text? The principle, however, could be justified by the arousal of the rhythmic sense on the reading of Juliano Saldanha’s hybrid literary piece “Introdução: Esse-menino-aí”, corpus of the present investigation. To achieve a possible critical reading of this literary piece striving for outlining its rhythm, as well as to devise a new concept of rhythm, are the aims of the present study. Starting from the assumption of an intensive rhythm induced by the performative movement on the reading process, it is intended to investigate the concepts related to the rhythm beyond the synonym between rhythm and metric. The theoretical foundation bases on Brik, Paz, Meschonnic, Zumthor, Gil, Pessoa, Deleuze e Nietzsche. The search is for a reading in the order of sensations and experiencing as well as for exposing the reading movements in the text construction, focusing on reaching the most adequate conception of intensive rhythm, enabling a broader range of possibilities on the investigation of Juliano Pessanha’s literary production